Marine Heatwaves Offshore Central and South Chile: Understanding Forcing Mechanisms During the Years 2016-2017 - Pujol, Cécile; Pérez-Santos, Iván; Barth, Alexander; Alvera-Azcárate, Aida (Frontiers in Marine Science, 2022)
Marine heatwaves (MHWs) are discrete warm-water anomalies events occurring in both open ocean and coastal areas. These phenomena have drawn researchers’ attention since the beginning of the 2010s, as their frequency and intensity are severely increasing due to global warming. Their impacts on the oceans are wide, affecting the ecosystems thus having repercussions on the economy by decreasing fisheries and aquaculture production. Chilean Patagonia (41° S-56° S) is characterised by fjord ecosystems already experiencing the global change effects in the form of large-scale and local modifications. This study aimed to realise a global assessment of the MHWs that have occurred along Central and South Chile between 1982 and 2020. We found that the frequency of MHWs was particularly high during the last decade offshore Northern Patagonia and that the duration of the events is increasing. During austral winter and spring 2016, combination of advected warm waters coming from the extratropical South Pacific Ocean and persisting high pressure inducing reduced winds have together diminished the heat transfer from the ocean to the atmosphere, creating optimal condition for a long-lasting MHW. That MHW hit Patagonia during 5 months, from May to October 2016, and was the longest MHW recorded over the 1982-2020 period. In addition, a global context of positive phases of El Niño Southern Oscillation and Southern Annular Mode contributed to the MHW formation.